Peter Paul Bajer, Scots in the Polish-Lithuanian Commonwealth, 16th–18th Centuries. The Formation and Disappearance of an Ethnic Group - Plakans, Andrejs (Journal of Northern Studies, 2013)
Review of: Peter Paul Bajer, Scots in the Polish-Lithuanian Commonwealth, 16th–18th Centuries. The Formation and Disappearance of an Ethnic Group (The Northern World. North Europe and the Baltic, c. 400–1700 AD. Peoples, Economies and Cultures 57), Leiden & Boston: Brill 2012, ISBN9789004212473, xxviii + 588 pp., index and illustrations.